Interactive cryptographic proofs of quantumness using mid-circuit measurements - Zhu, Daiwei; Kahanamoku-Meyer, Gregory D; Lewis, Laura; Noel, Crystal; Katz, Or; Harraz, Bahaa; Wang, Qingfeng; Risinger, Andrew; Feng, Lei; Biswas, Debopriyo; Egan, Laird; Gheorghiu, Alexandru; et al. (Nature physics, 2023)
The ability to perform measurements in the middle of a quantum circuit is a powerful resource. It underlies a wide range of applications, from remote state preparation to quantum error correction. Here we apply mid-circuit measurements for a particular task: demonstrating quantum computational advantage. The goal of such a demonstration is for a quantum device to perform a computational task that is infeasible for a classical device with comparable resources. In contrast to existing demonstrations, the distinguishing feature of our approach is that the classical verification process is efficient, both in asymptotic complexity and in practice. Furthermore, the classical hardness of performing the task is based upon well-established cryptographic assumptions. Protocols with these features are known as cryptographic proofs of quantumness. Using a trapped-ion quantum computer, we perform mid-circuit measurements by spatially isolating portions of the ion chain via shuttling. This enables us to implement two interactive cryptographic proofs of quantumness, which when suitably scaled to larger systems, promise the efficient verification of quantum computational advantage. Our methods can be applied to a range of interactive quantum protocols.Being able to perform qubit measurements within a quantum circuit and adapt to their outcome broadens the power of quantum computers. These mid-circuit measurements have now been used to implement a cryptographic proof of non-classical behaviour.